COVID-19 Epidemic in Pakistan: Review on Precautionary Measures (Law Policy, governance) and Impact on Pakistan - Ayesha Iqbal; Amjad Iqbal Falak (Yayasan Riset dan Pengembangan Intelektual, 2022)
The COVID-19 pandemic has ruined the worldwide economy. The study intended to evaluate the pandemic effects on the Pakistan economy, openly emphasizing economic growth and poverty alleviation and the efforts take to control pandemic in the country. The investigation discovered that the pandemic affects the financial development of the country, and the measure taken by the official though their policy law and good governance are the good initiatives to decrease pandemic effect in the country.